Quantum Information Processing with Alkali Atoms: A Narrative Review - Rashid, Muhammad; Husnain, Ayaz; Anwar, Hafiza Ayesha; Abbas, Aamir (The Nucleus, 2026)
Quantum information processing is a promising way that deals with the aspects of superposition, entanglement, computation using coherence, communication, and sensing. This review is an analysis of how alkali Rydberg atoms can be used in quantum information processing. The leading candidates are the alkali atoms, as they have a simple electronic structure, transitions that are well characterized, and which can be laser-cooled and trapped. Important mechanisms, such as EIT, dipole-dipole interactions, and Rydberg blockade, are necessary to achieve high-fidelity quantum gates, photon-photon interactions, and long-lived quantum memories. Experimental devices such as magneto-optical traps, optical tweezers, optical lattices, and warm vapor cells have made it possible to use a controllable atom-photon interface and scalable architecture. In the recent development of laser and microwave control methods, the time of coherence, state-transfer, and single-atom addressability have been enhanced. Such challenges include decoherence due to spontaneous emission, motional dephasing, and technical issues in trapping stability and laser linewidth. This review concludes that alkali Rydberg atoms, especially rubidium and cesium, are of relevance in scalable fault-tolerant quantum computing and quantum simulation, and represent the meeting of basic quantum science with new technology uses.